Fascinating interlocked triacontanuclear giant nanocages. Issue 85 (7th October 2021) - Bala, Sukhen; Akhtar, Sohel; Liu, Jun-Liang; Huang, Guo-Zhang; Wu, Si-Guo; De, Avik; Das, Krishna Sundar; Saha, Sayan; Tong, Ming-Liang; Mondal, Raju
Abstract : Three fascinating interlocked highly stable triacontanuclear giant nanocages were synthesized and structurally and microscopically characterized. The strong antiferromagnetic behaviour can be envisaged as a silver lining in generating elusive molecular nanomagnets. Abstract : We report herein three air, thermal and solvent stable interlocked triacontanuclear giant nanocages, generated using a node and spacer concept. Interestingly, the crystal structures of the cages are not only nano-dimensional but also exist in the nano-dimension range, which was corroborated with microscopic images. The combination of microscopic and crystallographic data, in effect, led us to a unique advantageous situation of generating nanomaterials with hard-to-come-by structural information at the molecular level.